Aspirin, ibuprofen, and reduced risk of advanced colorectal adenoma incidence and recurrence and colorectal cancer in the PLCO Cancer Screening Trial. Issue 17 (11th May 2021) - Chudy‐Onwugaje, Kenechukwu; Huang, Wen‐Yi; Su, L. Joseph; Purdue, Mark P.; Johnson, Christine C.; Wang, Lingxiao; Katki, Hormuzd A.; Barry, Kathryn Hughes; Berndt, Sonja I.
Abstract : Background: Studying the differential impact of aspirin and other nonsteroidal anti‐inflammatory drugs across the stages of colorectal neoplasia from early adenoma to cancer is critical for understanding the benefits of these widely used drugs. Methods: With 13 years of follow‐up, the authors prospectively evaluated the association between aspirin and ibuprofen use and incident distal adenoma (1221 cases), recurrent adenoma (862 cases), and incident colorectal cancer (CRC; 2826 cases) among men and women in the population‐based Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. With multivariable‐adjusted models, odds ratio (ORs) and 95% confidence intervals (CIs) for adenoma incidence and recurrence and hazard ratios (HRs) and 95% CIs for incident CRC were determined. Results: The authors observed a significantly reduced risk of incident adenoma with ibuprofen use (≥30 vs <4 pills per month: OR, 0.76 [95% CI, 0.60‐0.95]; P trend = .04), particularly advanced adenoma (OR, 0.48 [95% CI, 0.28‐0.83]; P trend = .005). Among those with a previous adenoma detected through screening, aspirin use was associated with a decreased risk of advanced recurrent adenoma (≥30 vs <4 pills per month: OR, 0.56 [95% CI, 0.36‐0.87]; P trend = 0.006). Both aspirin (HR, 0.88 [95% CI, 0.81‐0.96]; P trend <.0001) and ibuprofen use (HR, 0.81 [95% CI, 0.70‐0.93); P trend = 0.003) ≥30 versus <4 pills per month were significantly associated with reduced CRC risk. Conclusions: In this large prospective study with long‐term follow‐up, a beneficial role for not only aspirin, but also ibuprofen, in preventing advanced adenoma and curbing progression to recurrence and cancer among older adults was observed. Abstract : This large, population‐based, prospective study with long‐term follow‐up demonstrates a beneficial role for not only aspirin, but also ibuprofen, in preventing advanced adenoma and curbing progression to recurrence and cancer among older adults. The protection offered by these widely used nonsteroidal anti‐inflammatory drugs is notably significant against the development of advanced adenoma, an important target for intervention.